Membangun Komunikasi Yang Efektif Terhadap Kepuasan Kerja Karyawan: Peran Leader Member Exchange (LMX) Dalam Organisasi - Rofilah Rahadatul Aisyi; Diyana Syafitri; Deva Ekasani; Mohammad Rizqi; M. Isa Anshori (Jurnal Manajemen Bisnis Era Digital, 2024)
Leader-Member Exchange (LMX) is a concept that describes the dynamics of the relationship between a leader and each member of the work team in an organizational unit. LMX plays a crucial role in creating employee job satisfaction within an organization. This study aims to provide readers with a deeper understanding of the application of LMX theory in a corporate context, as well as its implications in managerial practice. Through this research, data from various sources are compared and analyzed, which come from several journals that are the main references. This research is an important first step in understanding the complex relationship between leaders and team members in an organization, and its consequences in achieving optimal organizational performance.